Comparison of mortality associated with respiratory viral infections between December 2019 and March 2020 with that of the previous year in Southeastern France. (July 2020) - Giraud-Gatineau, Audrey; Colson, Philippe; Jimeno, Marie-Thérèse; Zandotti, Christine; Ninove, Laetitia; Boschi, Céline; Lagier, Jean-Christophe; La Scola, Bernard; Chaudet, Hervé; Raoult, Didier
Highlights: There were fewer common respiratory virus-associated deaths in Southeastern France hospitals during 2019–2020 vs 2018–2019. The majority were due to decreases in influenza A virus and respiratory syncytial virus (RSV)-associated deaths. 55 deaths were associated with a SARS-CoV-2 diagnosis. There was similar respiratory virus-associated mortality among hospitalized patients. SARS-CoV-2 infections had a limited impact on the number of deaths of any cause among hospitalized people. Abstract: Respiratory viruses are a major cause of mortality worldwide and in France, where they cause several thousands of deaths every year. University Hospital Institute-Méditerranée Infection performs real-time surveillance of all diagnoses of infections and associated deaths in public hospitals in Marseille, Southeastern France. This study compared mortality associated with diagnoses of respiratory viruses during the colder months of 2018–2019 and 2019–2020 (week 47–week 14). In 2018–2019, 73 patients (0.17% of 42, 851 hospitalized patients) died after being diagnosed with a respiratory virus; 40 and 13 deaths occurred in patients diagnosed with influenza A virus and respiratory syncytial virus (RSV), respectively. In 2019–2020, 50 patients (0.10% of 49, 043 patients hospitalized) died after being diagnosed with a common respiratory virus; seven and seven deaths occurred in patients diagnosed with influenza A virus and RSV, respectively. Additionally, 55 patients died after being diagnosed with SARS-CoV-2. The proportion of respiratory virus-associated deaths among hospitalized patients was thus significantly lower for common respiratory viruses in 2019–2020 than in 2018–2019 (102 versus 170 per 100, 000 hospitalized patients; p = 0.003), primarily as a consequence of a decrease in influenza A virus (–83%) and RSV (–46%)-associated deaths. Overall, the proportion of respiratory virus-associated deaths among hospitalized patients was higher, but not significantly, in 2019–2020 than in 2018–2019 (214 versus 170 per 100, 000 hospitalized patients; p = 0.08, Yates-corrected Chi-square test). These findings put into perspective the death burden of SARS-CoV-2 infections in this geographical area.